Advances of Synthesis Methods for Porous Silicon-Based Anode Materials - Zhang, Fan; Zhu, Wenqiang; Li, Tingting; Yuan, Yuan; Yin, Jiang; Jiang, Jianhong; Yang, Lishan (Frontiers in Chemistry, 2022)
Silicon (Si)-based anode materials have been the promising candidates to replace commercial graphite, however, there are challenges in the practical applications of Si-based anode materials, including large volume expansion during Li+ insertion/deinsertion and low intrinsic conductivity. To address these problems existed for applications, nanostructured silicon materials, especially Si-based materials with three-dimensional (3D) porous structures have received extensive attention due to their unique advantages in accommodating volume expansion, transportation of lithium-ions, and convenient processing. In this review, we mainly summarize different synthesis methods of porous Si-based materials, including template-etching methods and self-assembly methods. Analysis of the strengths and shortages of the different methods is also provided. The morphology evolution and electrochemical effects of the porous structures on Si-based anodes of different methods are highlighted.